2020
DOI: 10.1186/s12871-020-01110-x
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative non-invasive versus semi-invasive cardiac index monitoring in patients with bariatric surgery – a prospective observational study

Abstract: Background: In morbidly obese patients undergoing laparoscopic bariatric surgery, the combination of obesityrelated comorbidities, pneumoperitoneum and extreme posture changes constitutes a high risk of perioperative hemodynamic complications. Thus, an advanced hemodynamic monitoring including continuous cardiac index (CI) assessment is desirable. While invasive catheterization may bear technical difficulties, transesophageal echocardiography is contraindicated due to the surgical procedure. Evidence on the cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…The majority of studies retrieved concerned the cardiovascular ( n = 14) [ 9 22 ], respiratory ( n = 7) [ 23 29 ], and neurological ( n = 9) [ 30 37 ] systems. Two pertained to point-of-care testing [ 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies retrieved concerned the cardiovascular ( n = 14) [ 9 22 ], respiratory ( n = 7) [ 23 29 ], and neurological ( n = 9) [ 30 37 ] systems. Two pertained to point-of-care testing [ 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies retrieved concerned the cardiovascular (n = 14) [9][10][11][12][13][14][15][16][17][18][19][20][21][22], respiratory (n = 7) [23][24][25][26][27][28][29], and neurological (n = 9) [30][31][32][33][34][35][36][37] systems. Two pertained to point-of-care testing [38,39].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have compared non-invasive BP measurement with a nger-cuff to direct BP measurement with an invasive arterial catheter in a variety of patients, without an explicit focus on patients after valve replacement surgery [20][21][22][23]. Those studies have shown that the measurement accuracy of the nger-cuff method is reduced in hypertensive patients and the elderly because peripheral small arteries such as the ngertips may be occluded or stenotic secondary to the effect of hypertension [7,24,25]. In these patients, measurement by the nger-cuff method may be di cult even if there are no anatomical abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…This is a planned secondary analysis of a single-center prospective observational cohort study where the comparison of continuous cardiac index measurements by Nexfin® and a semi-invasive reference method was previously published [ 28 ]. The single-center prospective observational cohort study was conducted at the Department of Anaesthesiology and Intensive Care Medicine and General Surgery, University Medical Center, Schleswig-Holstein, Campus Kiel, the protocol was approved by the local ethics committee of the Christian-Albrechts-University Kiel (file number: A 132/14).…”
Section: Methodsmentioning
confidence: 99%
“…A description of the study participants’ instrumentation, hemodynamic monitoring and anesthesia was already described previously [ 28 ].…”
Section: Methodsmentioning
confidence: 99%